2017
DOI: 10.1371/journal.pone.0189005
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysmal subarachnoid haemorrhage (aSAH): Five consecutive years' experience of Fars province, Iran

Abstract: ObjectiveSubarachnoid haemorrhage (SAH), caused by the rupture of intracranial aneurysms, is a devastating event with high rates of morbidity and mortality. Aneurysmal subarachnoid haemorrhage (aSAH) plays a critical role in the potential loss of life as its sufferers are usually of a young age. We aimed to investigate the incidence of aSAH along with the patients’ characteristics over five consecutive years in Fars, a large province located in Southern Iran.MethodsIn this prospective study, anonymous data of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The present study found an average age of 53.53 AE 9.64 years old, which is equivalent to the mean age of patients undergoing cerebral aneurysm surgery found in several studies. According to the study by Rahmanian et al, 14 among the 421 patients studied, an average of 49.8 AE 1.5 years old was found. According to a 2018 study, analyzing 2,898 patients, obtained an average of 58.9 AE 14.3 years old.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The present study found an average age of 53.53 AE 9.64 years old, which is equivalent to the mean age of patients undergoing cerebral aneurysm surgery found in several studies. According to the study by Rahmanian et al, 14 among the 421 patients studied, an average of 49.8 AE 1.5 years old was found. According to a 2018 study, analyzing 2,898 patients, obtained an average of 58.9 AE 14.3 years old.…”
Section: Discussionmentioning
confidence: 88%
“…According to a 2017 study, hypertension was observed in 47.1% of its patients. 14 In a study published in 2019, hypertensive patients corresponded to 43.82% of the sample. 17 A 2018 study showed that 31.2% were hypertensive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 5year investigation at our center, the MCA and the A-com a were the most commonly aneurysm sites among 421 aneurysmal subarachnoid cases. 2 In another study in our center, a significant correlation between levels of interleukin-1β (IL-1β) and outcome following aneurysmal SAH was found. 22 The mean age of the patients with ruptured and unruptured aneurysms was similar (about 49 years).…”
Section: Discussionmentioning
confidence: 96%
“…
Known risk factors for saccular aneurysm formation include hypertension, smoking, and various connective tissue disorders. 2 Computed tomography (CT) angiography, magnetic resonance angiography (MRA), and conventional angiography are Keywords ► cerebral aneurysm ► inflammation ► CD68 antigen ► Iran
…”
mentioning
confidence: 99%